Quality of Life, Anxiety, and Depression in Patients With Early-Stage Mycosis Fungoides and the Effect of Oral Psoralen Plus UV-A (PUVA) Photochemotherapy on it - Graier, Thomas; Fink-Puches, Regina; Porkert, Stephanie; Lang, Roland; Pöchlauer, Sophie; Ratzinger, Gudrun; Tanew, Adrian; Selhofer, Sylvia; Sator, Paul-Gunther; Hofer, Angelika; Gruber-Wackernagel, Alexandra; Legat, Franz J.; et al. (Frontiers in Medicine, 2020)
Background: Little is known about psychological discomfort and quality of life (QoL) in early stage mycosis fungoides (MF) and the effect of psoralen plus UV-A (PUVA) on it. Objective: To evaluate QoL, anxiety, and depression with validated instruments in early stage MF patients and whether PUVA treatment improves it. Methods: Patients with stage IA to IIA MF were treated with PUVA twice weekly for 12–24 weeks, followed by maintenance treatment or not, in a prospective randomized clinical trial. Patients completed a questionnaire on DLQI as well as the Hospital Anxiety and Depression Scale (HADS) prior to therapy, after their last PUVA exposure, and after the PUVA maintenance or observance phase. Results: For 24 patients with early stage MF, completed questionnaires were available and analyzed. Prior to treatment, 17% reported strong (DLQI > 10) and 29% moderate impairment (DLQI 6–10) in QoL; 33% of patients reported HADS scores indicating anxiety, and 21% reported scores indicating depression. PUVA significantly improved overall QoL by reducing mean DLQI scores by 58.6% (p = 0.003), HADS-A by 30% (p = 0.045), and HADS-D by 44% (p = 0.002). Improvements in QoL and psychological well-being seemed to be sustained, irrespective of maintenance treatment or not. Limitations: Small sample size. Conclusions: PUVA sustainably improves QoL and psychological well-being in patients with early stage MF. Clinical trial registration:ClinicalTrials.gov identifier: NCT01686594.